The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fendo.2020.608733
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Therapy in Graves’ Orbitopathy

Abstract: The balance of the cell redox state is a key point for the maintenance of cellular homeostasis. Increased reactive oxygen species (ROS) generation leads to oxidative damage of tissues, which is involved in the development of several diseases, including autoimmune diseases. Graves’ Orbitopathy (GO) is a disfiguring autoimmune-related condition associated with Graves’ Disease (GD). Patients with active, moderate-to-severe GO, are generally treated with high doses intravenous glucocorticoids (ivGCs) and/or orbita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Ma and his colleagues identified ferroptosis resistance in OFs cultured from TAO patients. These cells presented with higher viability than OFs obtained from healthy individuals after cystine deprivation, which is a frequently used method for stimulating the genesis of ferroptosis ( Lanzolla et al, 2020 ). In research on aging diseases, senescence was shown to make cells extremely resistant to ferroptosis due to the accumulation of intracellular iron ( Masaldan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ma and his colleagues identified ferroptosis resistance in OFs cultured from TAO patients. These cells presented with higher viability than OFs obtained from healthy individuals after cystine deprivation, which is a frequently used method for stimulating the genesis of ferroptosis ( Lanzolla et al, 2020 ). In research on aging diseases, senescence was shown to make cells extremely resistant to ferroptosis due to the accumulation of intracellular iron ( Masaldan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple potential antioxidants have been described in GO, including selenium, pentoxifylline, quercetin, enalapril, allopurinol, nicotinamide, vitamin C, N-acetylcysteine, melatonin, β-carotene, and statins [ 80 , 81 , 82 ]. A recent systematic review [ 80 ] included four clinical and ten in vitro studies from 1993 to 2018, and demonstrated that selenium was the only antioxidant based on in vitro and randomized controlled trial studies.…”
Section: Treatment For Tissue Remodeling In Gomentioning
confidence: 99%
“…The role of oxidative stress and selenium deficit has been also described. [21][22][23] A prospective observational study performed by EUGOGO to construct a predictive score for the occurrence and progression of GO in patients with recent onset GD has been recently performed. 24 Using mixed-effect logistic regression analysis, 4 determinants were identified, namely CAS, Thyroid-stimulating hormone (TSH)-binding inhibitor immunoglobulins, smoking, and longer duration of hyperthyroid symptoms.…”
Section: Go: Standard Treatment and Future Perspectivesmentioning
confidence: 99%